Kamus Aplikasi” sebagai media pendamping Buku ‘al-arabiyah al-mu’??iroh - Majidatun Ahmala (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2018)
The book al-‘Arabiyah al-mu’â?irah is an Arabic learning book designed that Arabic learners can master how to communicate in various conditions using modern Arabic. This study uses qualitative methods that emphasize the nature of research, data that comes from the reality in the field. Data collection techniques in this study were carried out by observations, interviews and documents in collecting data to be able to find out more about the problem, so that a problem solving can be arranged in accordance with the needs of the respondents. This study uses purposive sampling, sampling taken with certain reasons. Sampling taken by researchers is students of college who never studied Arabic before entering the Sunan Ampel UIN Surabaya. The purpose of this study is to determine the role of the application dictionary used by the teacher as a teaching companion from the book al-‘Arabiyah al-mu’â?irah.